Overvalued: Swedish monetary policy in the 1930s - Alexander Rathke; Tobias Straumann; Ulrich Woitek (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper reconsiders the role of monetary policy in Sweden's strong recovery from the Great Depression. The Riksbank in the 1930s is sometimes seen as an example of a central bank that was relatively innovative in terms of the conduct of monetary policy. To consider this analytically, we estimate a small-scale, structural general equilibrium model of a small open economy using Bayesian methods. We find that the model captures the key dynamics of the period surprisingly well. Importantly, our findings suggest that Sweden avoided the worst excesses of the depression by conducting conservative rather than innovative monetary policy. We find that, by keeping the Swedish krona undervalued to replenish foreign reserves, Sweden's exchange rate policy unintentionally contributed to the Swedish growth miracle of the 1930s, avoiding a major slump in 1932 and enabling the country to benefit quickly from the eventual recovery of world demand.
Keywords: C11; E58; F41; N14; 330; Geldpolitik; Wechselkurspolitik; Wirkungsanalyse; Konjunktur; Wirtschaftskrise; Wirtschaftsgeschichte; Schweden